New Molecular and Organelle Alterations Linked to Down Syndrome Heart Disease - Venegas-Zamora, Leslye; Bravo-Acuña, Francisco; Sigcho, Francisco; Gomez, Wileidy; Bustamante-Salazar, José; Pedrozo, Zully; Parra, Valentina (Frontiers in Genetics, 2022)
Down syndrome (DS) is a genetic disorder caused by a trisomy of the human chromosome 21 (Hsa21). Overexpression of Hsa21 genes that encode proteins and non-coding RNAs (ncRNAs) can disrupt several cellular functions and biological processes, especially in the heart. Congenital heart defects (CHDs) are present in 45–50% of individuals with DS. Here, we describe the genetic background of this condition (Hsa21 and non-Hsa21 genes), including the role of ncRNAs, and the relevance of these new players in the study of the pathophysiology of DS heart diseases. Additionally, we discuss several distinct pathways in cardiomyocytes which help maintain a functional heart, but that might trigger hypertrophy and oxidative stress when altered. Moreover, we highlight the importance of investigating how mitochondrial and lysosomal dysfunction could eventually contribute to understanding impaired heart function and development in subjects with the Hsa21 trisomy. Altogether, this review focuses on the newest insights about the gene expression, molecular pathways, and organelle alterations involved in the cardiac phenotype of DS.